Data for Leisure-time physical activities and their association with active behavior in other domains and sociodemographic aspects: a population-based study with adults residing in the Brazilian state capitals and the Federal District - Bertuol, Cecília (2022)
Dataset containing the supplementary materials regarding the characteristics of weekly frequency, duration, and intensity of physical activities during leisure-time, according to sociodemographic factors, among practitioners in the capitals of Brazil and the Federal District, 2017.